Highly efficient baculovirus-mediated multigene delivery in primary cells - Maysam Mansouri (Nature Portfolio, 2016)
Current viral gene delivery systems are limited in the amount of foreign DNA they can deliver to cells. Here the authors develop MultiPrime, a baculovirus-based vector system capable of multigene delivery into a wide variety of cells, and use Multiprime for genome engineering by CRISPR/Cas9.